Liposomal Bupivacaine Decreases Pain Scores and Narcotic Use After Cesarean Delivery [19E]. (May 2020) - Kindig, Marilyn; Mouch, Alexandra; Adams, Darren; Maxwell, Rose; Yaklic, Jerome
Abstract : INTRODUCTION: Liposomal bupivacaine (LB; Exparel 1.3%) is an extended-release, local anesthetic administered perioperatively for management of postoperative (PO) pain. When used as a liposomal suspension, bupivacaine has a fast onset of action with a duration up to 72 hours. This study examines patient reported pain scores (PRPain) and total morphine equivalents (ME) in patients receiving LB administration via transversus abdominis plane block (LB-TAP) or incisional infiltration (LB-II). METHODS: Women receiving LB-TAP (n=107) or LB-II (n=185) after cesarean delivery between January 2018 and January 2019 were included in the study. LB-TAP under ultrasound guidance and LB-II were performed by obstetrician-gynecologists. The infusion solution (80 mL, consisted of 20 ml 1.3% liposomal bupivacaine, 30 ml 1/2% bupivacaine and 30 ml injectable saline) was compounded by the pharmacy and sent to the operating room for injection. Primary endpoints are PRPain scores (10-point visual analog scale) and total PO ME used. RESULTS: Women receiving LB-TAP (5.5±1.6) reported higher PRPain than women receiving LB-II (4.6±1.7) on PO day 0 ( P <.001). However, groups did not differ on PRPain on PO day 1 or PO day 2. Groups were similar for total ME (LB-TAP=25.18 mg ±42.2 vs LB-II=24.92 mg ±51.3; P <.97). CONCLUSION: Our results show that initial differences in PRPain scores on PO day 0 for women receiving LB-TAP versus LB-II were not evident on PO day 1 or PO day 2. LB-TAP and LB-II resulted in similar ME, which was noted to be much lower than a recently published narcotics reducing protocol.